2020
DOI: 10.1007/s11010-020-03985-3
|View full text |Cite
|
Sign up to set email alerts
|

RIP1/RIP3/MLKL-mediated necroptosis contributes to vinblastine-induced myocardial damage

Abstract: Vinblastine (VBL) has been considered as a first-line anti-tumor drug for many years. However, vinblastine-caused myocardial damage has been continually reported. The underlying molecular mechanism of the myocardial damage remains unknown. Here, we show that vinblastine induces myocardial damage and necroptosis is involved in the vinblastine-induced myocardial damage both in vitro and in vivo. The results of WST-8 and flow cytometry analysis show that vinblastine causes damage to H9c2 cells, and the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…In contrast, a study conducted by Zhou et al showed that in vinblastine-induced rat myocardial injury, both MLKL level and phosphorylation of CaMKII were increased. Furthermore, the MLKL inhibitor necrosulfonamide (NSA) partially inhibited cell death [ 10 ]. Yang et al also found that both MLKL and CaMKII were phosphorylated in tissue samples gathered from mice exposed to a combined model of myocardial ischemia-reperfusion injury and chronic pain [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study conducted by Zhou et al showed that in vinblastine-induced rat myocardial injury, both MLKL level and phosphorylation of CaMKII were increased. Furthermore, the MLKL inhibitor necrosulfonamide (NSA) partially inhibited cell death [ 10 ]. Yang et al also found that both MLKL and CaMKII were phosphorylated in tissue samples gathered from mice exposed to a combined model of myocardial ischemia-reperfusion injury and chronic pain [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Zhang et al reported that during ischemia-reperfusion or doxorubicin-induced myocardial necroptosis, RIPK3 may signal through calcium/calmodulin-dependent protein kinase II (CaMKII) instead of MLKL [ 9 ]. Activation of CaMKII was also detected in vinblastine or tunicamycin-induced myocardial necroptosis, and in Bisphenol A-induced coronary endothelial cell necroptosis [ 10 , 11 , 12 ]. The precise roles of MLKL and CaMKII in SMC necroptosis remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis is involved in host defensive responses, chronic inflammation, and tissue damage, such as inflammation, hemolysis, and atherosclerosis ( Frank and Vince, 2019 ). The formation of receptor interacting protein kinase-1 and -3/mixed lineage kinase domain-like protein (RIP1/RIP3/MLKL)-containing complexes in necrotic bodies can initiate the necroptosis pathway ( Zhou et al, 2021 ). RPI1/RIP3/MLKL is expressed in ERMCs, and its content is higher than that in mitochondria.…”
Section: The Function Of Endoplasmic Reticulum-mitochondria Contactsmentioning
confidence: 99%
“…Mixed lineage kinase domain-like protein (MLKL) is the substrate of RIP3, and numerous studies have demonstrated that the formation of a complex between RIP3 and MLKL is an essential step for inducing programmed necrosis [ 15 , 16 ]. RIP3 and MLKL are significantly increased in vinblastine-caused myocardial damage [ 17 ]. Besides, inhibition of RIP3 and MLKL activation attenuates heart failure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%